2011
DOI: 10.1111/j.1365-2672.2011.04976.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of medium for indole-3-acetic acid production using Pantoea agglomerans strain PVM

Abstract: Aims:  To optimize the medium components for the production of indole‐3‐acetic acid (IAA) by isolated bacterium Pantoea agglomerans strain PVM. Methods and Results:  Present study deals with the production of an essential plant hormone IAA by a bacterial isolate P. agglomerans strain PVM identified by 16S rRNA gene sequence analysis. The medium containing 8 g l−1 of meat extract and 1 g l−1 of l‐tryptophan (precursor) at optimum pH 7, 30°C and 48‐h incubation gave the maximum production of IAA (2·191 g l−1). E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 23 publications
5
51
2
1
Order By: Relevance
“…2). Similar results were obtained with bacterial strains, namely Pantoea agglomerans PVM (Apine and Jadhav 2011), Streptomyces viridis CMU-H009 (Khamna et al 2010), Bacillus megaterium and Lactobacillus casei (Mohite 2013). However, Bacillus licheniformis produced higher amounts of IAA at 37 °C (Prashanth and Mathivanan 2010).…”
Section: Resultssupporting
confidence: 76%
“…2). Similar results were obtained with bacterial strains, namely Pantoea agglomerans PVM (Apine and Jadhav 2011), Streptomyces viridis CMU-H009 (Khamna et al 2010), Bacillus megaterium and Lactobacillus casei (Mohite 2013). However, Bacillus licheniformis produced higher amounts of IAA at 37 °C (Prashanth and Mathivanan 2010).…”
Section: Resultssupporting
confidence: 76%
“…Thokal et al [26] have also assessed the effect of pH values 4, 5, 6, 7 and 8 and they found pH 7 as optimum for their cultures. Pantoea agglomerans produced maximum IAA production at pH 7 [27].…”
Section: Discussionmentioning
confidence: 95%
“…The production of IAA was directly proportional to the incubation time and after 2 days of incubation IAA production enhanced by twofold, while in authors' own research presented in this paper, the amount of produced IAA doubled only after 7 days of incubation. Apine and Jadhav [39] obtained much higher concentrations of IAA. However, an inversed relationship was observed in this case, as with the increase in L-tryptophan concentration in the medium, the amount of determined IAA decreased.…”
Section: Resultsmentioning
confidence: 99%
“…2). In order to determine the abilities to produce IAA by tested strains P. agglomerans BC17 and BC45, the optimal conditions for bacterial growth was provided, that is 30 °C and pH 7, which was confirmed by Apine and Jadhav [39] in their research on the optimization of biosynthesis of IAA by P. agglomerans strain PVM. Under the same conditions, the authors obtained maximum amount of IAA 1530 µg/cm 3 at 30 °C and maximum amount of IAA 1441 µg/cm 3 at pH 7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation